Size-associated Variation and Factors Affecting the Morphology of Brown Bodies in Glycera tridactyla (Polychaeta:Glyceridae) - Can,Elif (2014)
Size-associated variations in brown body morphology (size and shape) were studied from the individuals of Glycera tridactyla. Variables related to size, length (BL) and width (BW) of the brown bodies were measured. On the basis of these measurements, other variables such as the surface area (SA), volume (V), surface area/volume ratio (SA/V) and elongation degree (ED) were calculated. Brown body shape was quantified by the elongation degree. The immature brown bodies were significantly smaller than the mature bodies, and therefore the smaller bodies had a higher SA/V. Results obtained from the regression analysis showed that there was a significant relationship between all the variables with the exception of SA/V:BW for the immature bodies and ED: BL for both groups of the bodies. The body size (proboscis length) of the worm and the sampling time (months) were the affecting factors on size and shape of the brown body. Brown bodies tend to be elongated as the proboscis length increased. The variation in size and/or shape of the brown bodies could refer to an adaptation to the movement along the coelomic fluid.